A Study of Using Massage Therapy Accompanied with Stretching Exercise for Rehabilitation of Mammary Gland Hyperplasia. (28th February 2016) - Lv, Pin; Chong, Yuping; Zou, Huagang; Chen, Xiangxian
Abstract : Purpose . To apply massage therapy accompanied with stretching exercises for treatment of mammary gland hyperplasia, evaluate the clinical outcome in patients, and estimate the therapy as a novel treatment method for mammary hyperplasia. Methods . 28 adult female patients were selected and treated with massage therapy and stretching exercises focusing on skeleton muscles of chest, abdomen, and axilla. The mammary gland oxyhemoglobin (OxyHb) and deoxyhemoglobin (DeoxyHb) levels were detected before and after treatment after 15, 30, and 45 days. Results . In this cohort, pretreatment OxyHb (mean ± SD) is 1.32 ± 0.14 (medium-high), and DeoxyHb is 0.87 ± 0.13 (normal). All patients were clinically diagnosed with benign mammary gland hyperplasia and mastitis. The posttreatment OxyHb levels are 1.23 ± 0.09 (normal-medium, 15-day), 1.16 ± 0.08 (normal, 30-day), and 1.05 ± 0.04 (normal, 45-day), and DeoxyHb levels are 0.90 ± 0.11 (normal, 15-day), 0.94 ± 0.18 (normal, 30-day), and 0.98 ± 0.12 (normal, 45-day). Patients were diagnosed with decreased hyperplasia 15 and 30 days after treatment and with no symptom of hyperplasia in mammary gland 45 days after treatment. Conclusion . Mammary gland hyperplasia is closely correlated with pathological changes of skeletal muscles and could be significantly improved by massage therapy and stretching exercises targeting neighboring skeletal muscles.